2012
DOI: 10.1002/cphc.201200428
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte‐Assisted Noncovalent Functionalization of Carbon Nanotubes with Ordered Self‐Assemblies of a Water‐Soluble Porphyrin

Abstract: The self-assembly and induced supramolecular chirality of meso-tetrakis(4-sulfonatophenyl)porphyrin (TSPP) on both single-wall (SWCNT) and multiwall carbon nanotubes (MWCNT) are investigated. Under mild pH conditions (pH 3), TSPP forms aggregates when CNTs are dispersed in an aqueous solution containing positively charged polyelectrolytes such as poly-L-lysine (PLL) or poly(allylamine hydrochloride) (PAH). Evidence for the geometry of the porphyrin aggregates is obtained from absorption spectra, whereby the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Other groups also dealt with the structure formation of TPPS with different polyelectrolytes or molecules: Bedard et al made hollow capsules consisting of TPPS and poly(allylamine hydrochloride) and poly(styrene sulfonate), which are able to produce active oxygen species by irradiation with laser light . Andrade et al investigated the interactions of TPPS with suspensions of different carbon nanotubes in presence of either poly‐ l ‐lysine or poly(allylamine hydrochloride) and revealed that the interaction depends on the diameter of the carbon nanotubes, the preparation time, the pH conditions, and on the polyelectrolyte architecture . Costa and co‐workers investigated the interactions of TPPS with polyamidoamine (PAMAM) dendrimers of generations 2 and 4 with steady‐state spectroscopy and time‐resolved fluorescence measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups also dealt with the structure formation of TPPS with different polyelectrolytes or molecules: Bedard et al made hollow capsules consisting of TPPS and poly(allylamine hydrochloride) and poly(styrene sulfonate), which are able to produce active oxygen species by irradiation with laser light . Andrade et al investigated the interactions of TPPS with suspensions of different carbon nanotubes in presence of either poly‐ l ‐lysine or poly(allylamine hydrochloride) and revealed that the interaction depends on the diameter of the carbon nanotubes, the preparation time, the pH conditions, and on the polyelectrolyte architecture . Costa and co‐workers investigated the interactions of TPPS with polyamidoamine (PAMAM) dendrimers of generations 2 and 4 with steady‐state spectroscopy and time‐resolved fluorescence measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence (PL) spectra were recorded at room temperature on a SPEX Fluorolog (Horiba Jobin Yvon) spectrofluorometer, using a 450 W Xe lamp as the excitation source and a solid sample holder to collect light at 22.5°, minimizing stray and reflected light from the sample surface. Fluorescence lifetime imaging microscopy (FLIM) measurements were performed on a time-resolved confocal microscope (MicroTime 200, PicoQuant GmbH) 48 . FLIM measurements of ZnO nanorods were made by taking random images (80 × 80 µm 2 ) throughout the coverslip; in each of these, another set of random (10 × 10 µm 2 ) images was also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…3 B it can be seen that, the presence of FeTSPP has a drastic effect on the morphology of the film, exhibiting cylindrical shaped filaments covered by polymer growing outwards. The explanation for this behaviour is the well‐known formation of porphyrin J aggregates in acidic aqueous solutions 34, which originates such tri‐dimensional arrangement. A six‐fold increase in the root mean square roughness ( R q ) from 2 nm with the PAn films to 12 nm, in the presence of the porphyrin moiety is observed.…”
Section: Resultsmentioning
confidence: 95%